How a YMCA work camp in the Philippines contributes to the improvement of a rural community - Pascual, Baceliza M. 1921- (1959)
The author aimed to present a detailed appraisal of a work camp undertaken by the Young Men Christian Association (YMCA) in a Philippine barrio and its effect on that community. She described how the YMCA work camp in Tonoton, Piddig, Ilocos Norte undertook rural improvement on different phase of community life through a self-help scheme.